The Influence of Digital Payment on Gen Z Financial Behavior with E-Wallet as Moderation on Students of Universitas Buana Perjuangan Karawang - Dhelzahra Yashinta; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
This study examines the impact of Digital Payment usage on the financial behavior of Gen Z students at Universitas Buana Perjuangan Karawang, with E-wallet as a moderating variable. The advancement of technology and the popularity of Digital Payments, such as E-wallets, offer transaction convenience but also influence financial management patterns, particularly among students. The study uses a descriptive quantitative method with primary data from 100 respondents, analyzed using SmartPLS 4. The results show that Digital Payment students financial behavior contributed 60.8%, with ease, speed, and transaction security as the main factors. However, E-Wallet does not act as a moderating variable, indicating that this technology has become part of student’s transaction habits without directly influencing their financial management. This study highlights the importance of improving digital financial literacy for students to manage finances more wisely and encourages Digital Payment service providers to address this need.